The present status of dialysis patients in Asian countries as of 2022 from a medical economic point of view - Toru Hyodo; Nobuhito Hirawa; Takahiro Kuragano; Yoshiaki Takemoto; Shunichiro Urabe; Saruultuvshin Adiya; Khurtsbayar Damdinsuren; Bukhchuluu Munaa; Alimaa Yondontsamts; Ariunbold Jamba; Munkhzul Dolgorsuren; Oyunchimeg Maamkhuu; et al. (Renal Replacement Therapy)
Abstract In Japan, Mongolia, and Indonesia, dialysis care has been covered by national health insurance and social welfare programs as of 2022, which covers much of the cost burden. However, the proportion of this burden varies by country and Japan is the only one of these countries in which medical fees are fully covered for all dialysis patients. As systems for dialysis medical care coverage have been established, the number of dialysis patients has increased dramatically in each country. However, the cost of dialysis treatment itself is very high relative to personal income in all countries. This puts pressure on national healthcare budgets and gives rise to concerns about the sustainability of dialysis care in the future. Peritoneal dialysis (PD) is less expensive than hemodialysis (HD) in Mongolia and Indonesia, and a PD-first policy is considered effective in reducing costs. Nevertheless, an overwhelming number of patients still undergo HD. Despite the difficulties faced by these three countries in obtaining funds for dialysis treatment, among Asian countries, Mongolia and Indonesia are considered to have relatively advanced healthcare systems. It is considered that there has been progress in the provision of dialysis treatment subsidies to the citizens of these countries.